2014
DOI: 10.1002/term.1970
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of chondroitinase ABC and glial cell line-derived neurotrophic factor from silk fibroin conduits enhances peripheral nerve regeneration

Abstract: Nerve conduits are a proven strategy for guiding axon regrowth following injury. This study compares degradable silk-trehalose films containing chondroitinase ABC (ChABC) and/or glial cell line-derived neurotrophic factor (GDNF) loaded within a silk fibroin-based nerve conduit in a rat sciatic nerve defect model. Four groups of silk conduits were prepared, with the following silk-trehalose films inserted into the conduit: (a) empty; (b) 1 µg GDNF; (3) 2 U ChABC; and (4) 1 µg GDNF/2 U ChABC. Drug release studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Enhancing the nerve conduit or scaffold itself with neurotrophic factors, such as glial-derived neurotrophic factor (GDNF), has proven to be an effective way to recruit Schwann cells and promote axonal regeneration. 46,47 Similarly, microspheres enhanced with nerve growth factors have been used to deliver growth factors to regenerating nerves with promising results. 48,49 Studies delivering insulin-like growth factor-1 (IGF-1) into the repair site show improved physical and functional recovery not only in young but also in aged animals.…”
Section: Future Directionsmentioning
confidence: 99%
“…Enhancing the nerve conduit or scaffold itself with neurotrophic factors, such as glial-derived neurotrophic factor (GDNF), has proven to be an effective way to recruit Schwann cells and promote axonal regeneration. 46,47 Similarly, microspheres enhanced with nerve growth factors have been used to deliver growth factors to regenerating nerves with promising results. 48,49 Studies delivering insulin-like growth factor-1 (IGF-1) into the repair site show improved physical and functional recovery not only in young but also in aged animals.…”
Section: Future Directionsmentioning
confidence: 99%
“…Engineered bionic conduit showed promising in vivo results [132]. Research has also reported the development of silk fibroin conduits loaded with nerve growth factors [133][134][135][136][137][138]. Despite the promising results, no silk conduit has yet been FDA approved.…”
Section: N-fibroinmentioning
confidence: 99%
“…This makes it a very strong candidate for treatment of human SCI. Moreover, ChABC also has the potential for wider therapeutic application, since it has recently been shown to improve outcome following peripheral nerve injury [10], and to promote cardiac sympathetic nerve regeneration following experimental myocardial infarction [11]. Additionally, there are an increasing number of studies describing beneficial results of the enzyme in experimental models of stroke [12,13].…”
Section: Introductionmentioning
confidence: 99%